PREGNANCY AND CHILDBIRTH IN WOMEN WITH COMBINED THROMBOPHILIA, HISTORY THROMBOSIS AND PREECLAMPSIA - D. L. Kapanadzhe (Акушерство, гинекология и репродукция)
A combination of multigenic thrombophilia with antiphospholipid syndrome is a high risk factor as venous and / or arterial thromboembolism, and a variety of obstetric and perinatal complications.